Achieving 12 Hour Normothermic Ex Situ Heart Perfusion: An Experience of 40 Porcine Hearts. Issue 4 (July 2016) - Trahanas, John M.; Witer, Lucas J.; Alghanem, Fares; Bryner, Benjamin S.; Iyengar, Amit; Hirschl, Jacob R.; Hoenerhoff, Mark J.; Potkay, Joseph A.; Bartlett, Robert H.; Rojas-Pena, Alvaro; Owens, Gabe E.; Bocks, Martin L.
Abstract : Although total body perfusion with extracorporeal life support (ECLS) can be maintained for weeks, individual organ perfusion beyond 12 hours has yet to be achieved clinically. Normothermic ex situ heart perfusion (ESHP) offers the potential for prolonged cardiac preservation. We developed an ESHP system to study the effect of perfusate variables on organ preservation, with the ultimate goal of extending organ perfusion for ≥24 hours. Forty porcine hearts were perfused for a target of 12 hours. Hearts that maintained electromechanical activity and had a <3× increase in vascular resistance were considered successful preservations. Perfusion variables, metabolic byproducts, and histopathology were monitored and sampled to identify factors associated with preservation failure. Twenty-two of 40 hearts were successfully preserved at 12 hours. Successful 12 hour experiments demonstrated lower potassium (4.3 ± 0.8 vs. 5.0 ± 1.2 mmol/L; p = 0.018) and lactate (3.5 ± 2.8 vs. 4.5 ± 2.9 mmol/L; p = 0.139) levels, and histopathology revealed less tissue damage ( p = 0.003) and less weight gain ( p = 0.072). Results of these early experiments suggest prolonged ESHP is feasible, and that elevated lactate and potassium levels are associated with organ failure. Further studies are necessary to identify the ideal perfusate for normothermic ESHP.